Designing, engineering, and analyzing reliable and efficient software - Singh, Hardeep, 1963-; Kaur, Kulwant, 1968- (Information Science Reference, 2013)
"This book discusses and analyzes various designs, systems, and advancements in software engineering, concenntrating on the integration of mathematics, computer science, and practices in engineering"--Provided by publisher